Electronic cigarette devices and oro-facial trauma (Literature review) - Ghazali, A.F.; Ismail, Ahmad Faisal; Daud, Azlina (IOP Science, 2017)
Detrimental effects of cigarette smoking have been well described and recognized globally. With recent advancement of technology, electronic cigarette has been introduced and gained its popularity and became a global trend, especially among young adults. However, the safety of the electronic devices remains debatable. This paper aimed to compile and review the reported cases of oro-facial trauma related to the usage of electronic cigarette devices. A literature search was conducted using PubMed/Medline in December 2016. The search terms used were a combination of “oral trauma”, “dental trauma”, “oral injury” and “electronic cigarette”. The search included all abstract published from the inception of the database until December 2016. Abstract that was written in English, case report, letter to editors, clinical and human studies were included for analysis. All selected abstract were searched for full articles. A total of 8 articles were included for review. All of the articles were published in 2016 with mostly case reports. The sample size of the studies ranged from 1 to 15 patients. Seven of the included articles are from United States of America and one from Mexico. Our review concluded that the use of electronic cigarette devices posed not only a safety concern but also that the devices were mostly unregulated. There should be a recognized authority body to regulate the safety and standard of the electronic devices.